2011
DOI: 10.1111/j.1365-2893.2011.01458.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of hepatitis B virus base core and precore/core promoter mutations on hepatocellular carcinoma in untreated older genotype C Chinese patients

Abstract: The aim of the study was to investigate the prevalence of mutations of basal core promoter (BCP) and precore (PreC) region of hepatitis B virus (HBV) and their association with hepatocellular carcinoma. A total of 341 untreated older HBV patients were divided into three groups: chronic hepatitis B (CHB, 185), cirrhotic hepatocellular carcinoma (LC-HCC, 113) and non-cirrhotic hepatocellular carcinoma (non-LC-HCC, 43). HBV BCP and PreC mutations and genotypes were determined by direct sequencing. Using univariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 33 publications
1
20
0
2
Order By: Relevance
“…[2,46] The results support the conclusion that each of these mutations (A1762T, G1764A, and A1762T/G1764A) plays a significant role in the progression of chronic HBV infection to HCC. [38,43,47,48] The risk of HCC associated with the double mutation A1762T/G1764A was similar to those described in previous meta-analyses. [5,17] The data show a similar risk of HCC associated with A1762T, G1764A, and A1762T/G1764A with OR of 3.96, 3.48, and 3.96, respectively.…”
Section: Discussionsupporting
confidence: 83%
“…[2,46] The results support the conclusion that each of these mutations (A1762T, G1764A, and A1762T/G1764A) plays a significant role in the progression of chronic HBV infection to HCC. [38,43,47,48] The risk of HCC associated with the double mutation A1762T/G1764A was similar to those described in previous meta-analyses. [5,17] The data show a similar risk of HCC associated with A1762T, G1764A, and A1762T/G1764A with OR of 3.96, 3.48, and 3.96, respectively.…”
Section: Discussionsupporting
confidence: 83%
“…The lower rate of underlying cirrhosis in HBV-related HCCs as compared to other etiologies argues for a more direct role of HBV in the oncogenetic process. [8] The molecular and genetic features of HBV chronic infection involving cancer development could be summarized into (1) Pre-core and basal core promoter mutations, genotype B and C [9][10][11][12][13] and (2) integration of HBV DNA into the host genome and the expression of HBV proteins such as surface proteins and the X protein. [14][15][16] Studies on the natural history of chronic HBV infection have shown that active HBV replication contributes to the development of acute hepatitis flare, hepatic decompensation, cirrhosis, and HCC.…”
Section: Hbvmentioning
confidence: 99%
“…As for pre-S deletion, it was (Gao et al, 2007) reported that these mutations were more commonly found in the patients with HCC that in the chronic hepatitis B or asymptomatic carrier, suggesting pre-S deletion might involved in HBV-related hepatocarinogenesis. Mutations in basal core promoter may also involved in the development of carcinoma, the result of direct sequencing revealed that mutations including A1896, A1899 and multiple mutations T1762/A1764+A1896, T1762/A1764+A1899, and T1762/A1764+A1896+A1899 were more common in cirrhotic hepatocellular carcinoma group and non-cirrhotic hepatocellular carcinoma than chronic hepatitis B patients (Zheng et al, 2011). Moreover, a study with 37 patients and 38 controls has been performed and reported G1613A and C1653T double mutations were more prevalent in patients with HCC, thus, those mutations may serve as makers in predicting HCC development (Tatsukawa et al, 2011).…”
Section: Hbv Infectionmentioning
confidence: 99%